Deskripsi Keterampilan Komunikasi dan Kolaborasi Siswa SMA pada Pembelajaran Titrasi Asam-Basa dengan Model Inkuiri Terbimbing dan Berbasis Masalah - Novita Rizal; Zonalia Fitriza (Universitas Negeri Padang, 2021)
The research objective was to describe the communication and collaboration skills of high school students in learning acid-base titration with guided inquiry and problem-based models. This type of research is library research with descriptive analysis. Secondary data used are literature in the form of books, journals and assessment rubrics. The data collection method is a documentation method with Miles and Huberman data analysis. Based on the results of the literature review, it was found that students communication and collaboration skills in learning acid-base titration with guided inquiry and problem-based models occurred at each stage. Acid-base titration learning activities using guided and problem-based inquiry models train communication skills when discussing, asking, answering oral and written questions and collaborating when working together in class or in the laboratory.